Circular Economy for Sustainable Communities and Lifestyles: The Wisdom of the Jomon People across 10,000 Years of Time and Space - Yasuyuki Yamaoka (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
In this paper, the value of Japan's ancient 10,000-year-long Jomon culture is re-explored. They lived a cooperative lifestyle rather than depriving the other side of resources in inter-tribal conflicts. They also did not oppress nature, but received the minimum resources necessary for the people of the village to survive from nature, which changed from season to season. Previous studies have dismissed the lack of organised agriculture as pre-civilisational, and it has been assumed that they made their living by hunting animals and gathering nuts. However, the use of storage warehouses showed that they had established a balance between planned food gathering and consumption. The lack of organised agriculture was rather an excellent system that did not create classes in the social structure. It is astonishing that the Jomon people were already implementing the ideas that form the basis of the modern SDGs. Across time and space, modern people should humbly learn from the Jomon people.